2017
DOI: 10.1007/s00167-017-4820-3
|View full text |Cite
|
Sign up to set email alerts
|

Lower complication rate and faster return to sports in patients with acute syndesmotic rupture treated with a new knotless suture button device

Abstract: Randomized controlled trial, Level I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 34 publications
1
79
0
Order By: Relevance
“…Three studies included ankle fractures with syndesmosis disruption, 4,13,14 and 2 studies included patients with acute isolated syndesmosis disruption and with ankle fracture associated with syndesmosis disruption. 1,5 Table 2 summarizes the outcomes of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies included ankle fractures with syndesmosis disruption, 4,13,14 and 2 studies included patients with acute isolated syndesmosis disruption and with ankle fracture associated with syndesmosis disruption. 1,5 Table 2 summarizes the outcomes of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, late tibioperoneal diastasis can be regarded as a common finding after screw removal, as already described by other authors, 29 and recurrent diastasis or instability could occur. 1,5…”
Section: Discussionmentioning
confidence: 99%
“…The restoration of more physiologic movements of the syndesmosis obtained with dynamic devices could have contributed to faster healing and clinical recovery. 16 In fact, a shorter time to return to work and sports activity was reported in 2 studies, 5,19 even with consideration that a standardized rehabilitation protocol was used in the 2 groups (despite the possibility of early weightbearing in the case of dynamic fixation). Another theoretical advantage of dynamic fixation, especially with suture buttons, is that it may allow more motion and improved self-centering of the syndesmosis, thus making anatomic reduction easier to accomplish.…”
Section: Discussionmentioning
confidence: 99%
“…Several fixation methods such as suture-button fixation, tightrope fixation, and syndesmotic hook fixation have been used in the treatment of distal tibiofibular syndesmosis injury, and satisfactory outcomes have been achieved using these methods. [ 25 , 32 , 33 ] Recently, suture-button techniques have been popularized for the treatment of distal tibiofibular syndesmosis injury, and several studies have reported that suture-button fixation can achieve satisfactory outcomes. [ 25 , 33 – 38 ] A recent systematic review reported that suture-button fixation is associated with a better objective range of motion, an earlier return to work, and lower rates of implant removal, implant failure, and malreduction, compared with screw fixation, though similar functional outcomes as measured by the AOFAS score and postoperative complication rates were found.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 , 32 , 33 ] Recently, suture-button techniques have been popularized for the treatment of distal tibiofibular syndesmosis injury, and several studies have reported that suture-button fixation can achieve satisfactory outcomes. [ 25 , 33 – 38 ] A recent systematic review reported that suture-button fixation is associated with a better objective range of motion, an earlier return to work, and lower rates of implant removal, implant failure, and malreduction, compared with screw fixation, though similar functional outcomes as measured by the AOFAS score and postoperative complication rates were found. [ 15 ] In addition, a meta-analysis by Gan et al has reported that dynamic fixation using suture-button fixation results in similar clinical outcomes for the treatment of distal tibiofibular syndesmosis injury compared with static fixation using screw fixation but is associated with a reduced requirement for secondary intervention.…”
Section: Discussionmentioning
confidence: 99%